Ovarian torsion in the canal of nuck of a full-term female infant - Reem AlBuainain; Wael Tahseen; Abdulrahim AlSayed (Elsevier, 2021)
Canal of nuck hernia is an important differential diagnosis of an inguinal swelling in a pediatric female. A known risk factor is prematurity. An ovary, with or without the fallopian tube, is a common finding within the hernial sac, and when compared to intestinal loops, ovaries are at higher risk of incarceration. Incarcerated ovaries are at risk of developing torsion. Optimal timing for surgical repair of an ovarian hernia remains controversial. Detorsion is the mainstay in management of ovarian torsion. Prompt surgical management is essential to prevent ovarian necrosis.We present a case of ovarian torsion in a full-term female infant presenting with right inguinal swelling. The diagnosis was made clinically and with the aid of ultrasound. The patient underwent open operative repair. The hernial sac was explored and revealed non-viable right adnexa. Right oophorectomy and salpingectomy was made and the defect was repaired with high ligation of the sac. Post-operative stay was uneventful.